Production Of Biomass, Total Saponin And Proline Under Varied Nitrogen Concentration In Suspension Cultures Of Gymnema Sylvestre R. Br (Applied Biological Research, 2017)
Plants generally have medicinal value based on the kind and concentration of secondary  metabolites they possess. One of such medicinally important plant Gymnema sylvestre R.Br.  (Aslepiadaceae), commonly called ‘gurmar’, has widely been used in ayurvedic and homoepathic  systems of medicine. Traditionally, this plant is used for its anti-diabetic potential attributed to the  saponin named as gymnemic acid (Min et al., 2007). The nitrogen concentration in medium greatly  influences the amount of secondary metabolite produced (Nagella and Murthy, 2011) as it is  required for the expression of specific proteins (Sugiharto and Sugiyama, 1992). The NH4+ to NO3- ratio influences the amount of biomass produced (Nagella and Murthy, 2011). Secondary  metabolites are accumulated in cells in response to biotic and abiotic stress. Proline is one of the  compounds accumulated in response to stress (Yaish, 2015). The present study aimed to analyze the  influence of nitrogen on biomass and total saponin production in G. sylvestre, through a cost
Keywords: Biomass; Saponin; Concentration; Suspension Cultures